IMPLEMENTASI GERAKAN PEMBUDAYAAN PERTANIAN PERKOTAAN DI KECAMATAN BANYUMANIK KOTA SEMARANG - Rizqa Alya, Farah; Puspo Priyadi, Budi; Kismartini, Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Urban Farming is an alternative to farming on narrow land, especially in densely populated urban areas. The Urban Agricultural Cultivation Movement is a movement based on Semarang Mayor Regulation no. 24 of 2021 carried out by the Semarang City Government and the Semarang City Agriculture Service. Banyumanik District is an area that has been successful in implementing the Urban Agricultural Cultivation Movement. This is proven by the 5 (five) dimensions in Semarang City Perwal No. 24 of 2021 which is a reference in implementing the Urban Agricultural Cultivation Movement. This research aims to analyze the implementation of the Urban Agricultural Civilization Movement in Banyumanik District, Semarang City as well as the factors driving the success of the implementation of the Urban Agricultural Civilization Movement. This research uses a qualitative descriptive method by collecting data through observation, interviews and documentation techniques. The results of the research show that the implementation of the Urban Agricultural Cultivation Movement in Banyumanik District, Semarang City has achieved success based on the five dimensions of Semarang City Perwal No. 24 of 2021 which consists of the Urban Agriculture Cultivation Movement, Urban Agriculture Facilitation, Urban Farming Corner, Monitoring and Evaluation, and Financing. The driving factors for the successful implementation of the Urban Agricultural Cultivation Movement in Banyumanik District, Semarang City consist of communication, resources, disposition and bureaucratic structure.